Analysis of nucleophosmin–anaplastic lymphoma kinase (NPM‐ALK)‐reactive CD8+ T cell responses in children with NPM‐ALK+ anaplastic large cell lymphoma. (16th August 2016) - K. Singh, V.; Werner, S.; Hackstein, H.; Lennerz, V.; Reiter, A.; Wölfel, T.; Damm‐Welk, C.; Woessmann, W.
Summary: Cellular immune responses against the oncoantigen anaplastic lymphoma kinase (ALK) in patients with ALK‐positive anaplastic large cell lymphoma (ALCL) have been detected using peptide‐based approaches in individuals preselected for human leucocyte antigen (HLA)‐A*02:01. In this study, we aimed to evaluate nucleophosmin (NPM)‐ALK‐specific CD8 + T cell responses in ALCL patients ensuring endogenous peptide processing of ALK antigens and avoiding HLA preselection. We also examined the HLA class I restriction of ALK‐specific CD8 + T cells. Autologous dendritic cells (DCs) transfected with in‐vitro ‐transcribed RNA (IVT‐RNA) encoding NPM–ALK were used as antigen‐presenting cells for T cell stimulation. Responder T lymphocytes were tested in interferon‐gamma enzyme‐linked immunospot (ELISPOT) assays with NPM–ALK‐transfected autologous DCs as well as CV‐1 in Origin with SV40 genes (COS‐7) cells co‐transfected with genes encoding the patients' HLA class I alleles and with NPM–ALK encoding cDNA to verify responses and define the HLA restrictions of specific T cell responses. NPM–ALK‐specific CD8 + T cell responses were detected in three of five ALK‐positive ALCL patients tested between 1 and 13 years after diagnosis. The three patients had also maintained anti‐ALK antibody responses. No reactivity was detected in samples from five healthy donors. The NPM–ALK‐specific CD8 + T cell responses were restricted by HLA‐C‐alleles (C*06:02 and C*12:02) in all three cases. This approach allowed for the detection of NPM–ALK‐reactive T cells, irrespective of the individual HLA status, up to 9 years after ALCL diagnosis. Abstract : We aimed to evaluate nucleophosmin (NPM)‐ALK‐specific CD8 + T cell responses in ALCL patients ensuring endogenous peptide processing of ALK antigens and avoiding HLA‐preselection. NPM‐ALK‐specific CD8 + T cell responses were detected in three out of five ALK‐positive ALCL patients tested between 1 and 13 years after diagnosis. The NPM‐ALK specific CD8 + T cell responses were restricted by HLA‐C‐alleles (C*06:02 and C*12:02) in all three cases.